Animal Welfare and Social Innovation: Evidence from a Case Study in Southern Brazil - Zawaki Pazetto, Alexandre; Nunes, Nei Antonio; da Silva Leite, André Luis (Organizações & Sociedade, 2021)
This study examined the Cão Terapia (Dog Therapy) project, developed by a civil society organization, in order to verify how it generates social innovation based on practices focused on animal welfare. It is a qualitative case study, with an exploratory and descriptive approach. It consists of literature review, documentary research, participant observation, and interviews with volunteers and managers of the Bem-Animal organization. Bem-Animal seeks to promote the welfare of animals rescued by the government after complaints of abuse, being run over, and other serious situations. We found that the initiatives of this organization result in social innovation, above all, by providing social actions contrary to the speciesist, instrumental, and consumerist mentalities. They contribute to an experience of ethical precepts and to the consolidation of rights for non-human animals within the society.